An Alternate Technique for Goniotomy: Description of Procedure and Preliminary Results - Shute, Thomas; Green, Wesley; Liu, James; Sheybani, Arsham (Journal of Ophthalmic and Vision Research, 2022)
Purpose: Multiple glaucoma treatment modalities seek to lower IOP by bypassing or removing a portion of the juxtacanalicular trabecular meshwork. These procedures often require expensive implants or specialized surgical instruments. The authors developed a technique for ab interno goniectomy utilizing a standard disposable 25-gauge hypodermic needle. The surgical procedure—termed bent ab interno needle goniectomy (BANG)—and preliminary results are presented here. Methods: A retrospective chart review was performed for all patients who underwent goniotomy using a modified hypodermic needle by one of the three authors between July 2017 and June 2018. The mean and standard deviation pre- and postoperative IOP and the number of glaucoma medications were calculated. The student paired t-test was used to compare pre- and postoperative data. A P-value of <0.05 was considered statistically significant. Results: At postoperative month six, the mean IOP was 13.3 ± 2.5 mmHg (P = 3.6 × 10−7) on 0.5 ± 0.8 topical glaucoma medications (P = 0.01). A ≥20% reduction in IOP was achieved in 73% of patients. Seventy-three percent of patients required ≥1 fewer medication, while 73% of patients required no medications for IOP control. Forty-one percent of those treated achieved IOP ≤12 mmHg. Conclusion: The BANG procedure is a low-cost MIGS technique available to surgeons around the world with preliminary outcomes similar to more expensive alternatives.